OPTIMIZATION OF SURGICAL TREATMENT OF VERTEBRAL ARTERY TORTUOSITY - D.D. SULTANOV; A.D. GAIBOV; O. NEMATZODA; KH.A. YUNUSOV (Avicenna Tajik State Medical University, 2020)
Objective: Analysis of the results of standard and optimized surgical treatment of vertebral artery (VA) tortuosity. Methods: The results of surgical treatment of 52 patients with VA tortuosity were analyzed. There were 18 men (34.6%), and 34 women (65.4%). The age of patients ranged from 23 to 75 years. C- and S-shaped kicking of VA occurred in 38 cases, coiling in 8 cases and Powers syndrome in 6 cases. In 28 (53.8%) patients there was also hypoplasia of the contralateral VA, and in 7 (13.5%) cases there was a pathological deformation of the internal carotid artery. Results: Depending on the shape of the tortuosity, 4 techniques of reconstructive operations were performed to eliminate tortuosity. In the postoperative period thrombosis of the anastomosis line noted in 2.8% of cases, TIA - in 1.9%, and stroke - in 1.9%. The immediate and long-term results in the groups showed the effectiveness and best results in the group of patients who underwent lateralization of the VA of the author's modification. Also established that for VA coiling, the method of choice is to move and implantation of VA into the carotid artery. Conclusion: Correction of VA tortuosity should be differentiated, and the choice of the method of surgery technique should depend on the type of tortuosity and concomitant vascular pathology. The lateral and anterior moving VA ostium helps to reduce the rate of anastomosis thrombosis and greatly facilitates the surgery technique.